Proceedings of the 2016 3rd International Conference on Materials Engineering, Manufacturing Technology and Control 2016
DOI: 10.2991/icmemtc-16.2016.141
|View full text |Cite
|
Sign up to set email alerts
|

A COMSOL modeling of the pre-breakdown heating phase in the electro-thermal breakdown of conductive water

Abstract: Abstract. By using the multi-physics simulation software COMSOL, the pre-breakdown-heating phase in the electro-thermal breakdown of conductive water is modeled. In this COMSOL model, the Joule-heating module (jh) and the electric circuit module (cir) are used together to simulate the time-evolution of the temperature in the central axis of the underwater gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Calculation of the dynamics of the formation of a gas bubble in water and its heating under the influence of the voltage applied to the electrodes by the electrothermal model at electric field strength up to 10 kV/cm is given in [5]. The use of a multiphysical calculation model in the COMSOL program showed that a discharge in water with a conductivity of 3 S/m of a 5 mF storage capacitance charged to a voltage of 3 kV leads to an increase in the temperature in the interelectrode gap to (300-800) K and the transition of water to a vapor state.…”
mentioning
confidence: 99%
“…Calculation of the dynamics of the formation of a gas bubble in water and its heating under the influence of the voltage applied to the electrodes by the electrothermal model at electric field strength up to 10 kV/cm is given in [5]. The use of a multiphysical calculation model in the COMSOL program showed that a discharge in water with a conductivity of 3 S/m of a 5 mF storage capacitance charged to a voltage of 3 kV leads to an increase in the temperature in the interelectrode gap to (300-800) K and the transition of water to a vapor state.…”
mentioning
confidence: 99%